Chinese Muslims in Transregional Spaces of Mainland China, Taiwan, and Beyond in the Twentieth Century - Cieciura, Wlodzimierz (Review of Religion and Chinese Society, 2018)
This article examines the modern social history of Chinese Hui Muslims in the context of transregional connections within and beyond the borders of the two modern Chinese nation-states, the People's Republic of China and the Republic of China on Taiwan. The article applies Engseng Ho's concepts for the study of Inter-Asia to the biographical study of several prominent Hui religious professionals and intellectuals. The experiences and personal contributions to the development of modern Chinese Muslim culture of people like Imam Ma Songting are scrutinized, along with political and ideological conflicts over different visions of Chineseness and "Huiness" during the turbulent twentieth century. It is argued that when studying the social history of Chinese Muslims, researchers should not limit themselves to the religious activities of Hui elites that occurred within the confines of the two Chinese nation-states, but should also take into consideration the expansion of those elites' religious activities abroad and the intensive circulation of knowledge across Inter-Asian spaces in which they participated.